Characterization of the peak temperature on upper W divertor target during D and He plasma discharges in EAST. (March 2023) - Yu, Baixue; Zhu, Dahuan; Li, Changjun; Xuan, Chuannan; Ding, Rui; Gao, Binfu; Chen, Junling; Du, Chun; ,
Highlights: The peak temperature on observed targets during both D and He discharges increase with the increase of heating power. During the same heating power, the peak temperature during D discharges is generally lower than that during He discharges no matter L and H modes. The sharp temperature leap induced by ELM induced transient heat load during D discharges is usually 2 times higher than that during He discharges. Abstract: During the tokamak plasma discharge, the strong interaction between the edge plasma and the wall material leads to the overheating of the surface of divertor target plate and the possible melting of the material, which will seriously influence the safe operation of the device. Furthermore, transient heat load induced by edge localized modes (ELMs) is expected to cause surface damage of tungsten (W) based plasma-facing materials (PFMs) in future fusion devices. In order to ensure safe steady-state operation, it is prerequisite to obtain the peak temperature as well as distribution on the divertor target plate in real time. In EAST, a high temporal and spatial resolution infrared camera (IR) located in H port was built to observe the outer target on the L port of upper W divertor. Currently, the maximum temperature measured by IR camera has been characterized and analyzed during deuterium (D) and helium (He) plasma discharges. In addition, the ELM-induced temperature rise during H mode operations for D and He plasma discharges was specially studied. It is found that the maximum temperature on observed targets during both D and He discharges increase with the increase of heating power. In case of the same heating power, the maximum temperature during D discharges is generally lower than that during He discharges no matter L and H modes, which is more obvious when the total heating power exceeds 3 MW. However, the sharp temperature rise by ELM induced transient heat load during D discharges is usually higher than that during He discharges. Such qualitative and statistical analysis on the maximum temperature on upper outer divertor provides important reference for future operation of EAST and other tokamaks.